Diagnostic accuracy of periapical radiolucency using periapical radiography and cone-beam computed tomography - I Putu Gede Andyka Yasa; Haris Nasutianto; Tomohiro Okano (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: This research is aimed to compare the accuracy of periapical radiography in detecting periapical radiolucency with that of Cone-beam Computed Tomography (CBCT) and to assess the additional information that CBCT provides. Materials and Methods: 96 patients with a primary diagnosis of endodontic problem had been studied retrospectively. Each root was examined for the presence or absence of periapical lesions according to the Periapical Index (PAI) Score. Roots and root canals identified through perapical radiography and CBCT were recorded. Additional information from CBCT regarding effects of lesions in cortical bone and maxillary sinus was also noted. Sensitivity, specificity, positive predictive value, and negative predictive value were analyzed. Results: The result showed that accuracy of periapical radiography as expressed by its sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) was 0.65, 0.90, 0.86, 0.75, respectively. Conclusion: Periapical radiography has a low sensitivity in detecting periapical lesions compared to CBCT. CBCT also provides more detailed information that is useful in endodontic treatment.